THE RHYTHM AND DANCE AS PART OF THE PSYCHOMOTOR DEVELOPMENT PROCESS OF PEOPLE WITH DOWN SYNDROME: THE LABAN METHOD AS METHODOLOGICAL SUBSIDY (Fiep Bulletin - online, 2012)
This study aimed to analyze the contents of rhythm and dance as a teaching strategy for psychomotor stimulation of people with Down syndrome, stimulating and enabling new opportunities so that they could develop multilaterally. it was possible through the methodology of Laban. This methodology provides a practice based on student's reality, where there is no standardization of motion and the greater focus is on creating the potential of individuals, the dance could contribute to several aspects of development of each one as: balance, memory, coordination among others, making contributions in the psychomotor development and social inclusion of these people.
Keywords: Down Syndrome; psychomotor; dance